Customary Justice and Child Sexual Abuse in Aceh: Legal Pluralism, Restorative Limits, and Child Protection Principles - Yuni Roslaili; Suparwany Suparwany; Abdul Manan; Marina Ulfah; Faizah Putroe Phonna (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study explores the position and limitations of customary law in addressing cases of child sexual violence in Aceh, as well as its interaction with legal pluralism and the principles of maqaṣid al-sharia. As a region endowed with special autonomy in the spheres of customary practices and the implementation of Islamic law, Aceh represents a complex manifestation of legal pluralism. This complexity becomes particularly evident when customary dispute-resolution mechanisms intersect with cases of child sexual violence, which are normatively recognised as serious criminal offences. By using a qualitative socio-legal approach, this research integrates an analysis of statutory regulations and qanun (Islamic law) with in-depth interviews involving government officials, local leaders, academic communities, and child protection institutions. The findings reveal variations in the application of customary law to cases of sexual violence against children, which can be classified into minor, moderate, and severe categories. In minor cases, customary law may function as a limited mechanism for recovery and social reconciliation. However, in cases of severe sexual violence, formal judicial processes are deemed more appropriate. This is because, from the perspective of maqasid al-sharia and the concept of ta’zir, child protection is a daruriyyah goal that cannot be compromised. This study emphasises the importance of an integrative-complementary model for resolving child sexual abuse cases within the framework of controlled legal pluralism.